Antioxidant enzyme influences germination, stress tolerance, and virulence of Isaria fumosorosea. (11th June 2013) - Ali, Shaukat; Huang, Zhen; Li, Huaxing; Bashir, Muhammad Hamid; Ren, Shunxiang
Abstract Antioxidizing enzymes (superoxide dismutase, catalase, and glutathione peroxidae) are important enzymatic systems used to degrade hydrogen peroxide into water and oxygen, thereby lowering intracellular hydrogen peroxide levels. Entomopathogenic fungi display increased activities of antioxidizing enzymes during growth and germination, which is necessary to counteract the hyperoxidant state produced by oxidative metabolism. We studied the influence of different carbon sources on antioxidizing enzyme production by Isaria fumosorosea to determine the importance of antioxiding enzymes induction in fungal germination, stress tolerance and virulence. Conidia produced by colonies grown on hydrocarbons showed higher rates of enzyme activities compared to the control and the enzyme activities of the conidia produced on n‐octacosane were higher than all the other treatments. The lipid peroxidation activities were observed as an indicative marker of oxidative damage to cells and the lowest levels of lipid peroxidation activities were observed for n‐octacosane treatment. The increased enzyme activities of n‐octacosane‐ grown conidia were accompanied by higher levels of resistance to exogenous hydrogen peroxide, reduction in germination time and higher virulence against Spodoptera exigua. Our study has helped to identify that increased activities of antioxidizing enzymes can improve the germination and tolerance to antioxidant stress response of I. fumosorosea.